A Pilot HRCT Follow-Up Study to Test the Feasibility of Predictive Efficacy of Serum Periostin in Idiopathic Pulmonary Fibrosis - Liu M; Cheng ZJ; Chen J; Li H; Xue M; Fu X; Li Y; Wang J; You C; Hu H; Wu H; Huang H; et al. (Dove Medical Press, 2024)
Mingtao Liu,1,* Zhangkai J Cheng,1,* Jiaxi Chen,2,* Haiyang Li,1,3 Mingshan Xue,4,5 Xing Fu,1 Yanjun Li,2 Jiaxin Wang,2 Chenwei You,2 Haisheng Hu,1 Haojie Wu,1 Huimin Huang,1 Baoqing Sun1,4 1Department of Clinical Laboratory of the First Affiliated Hospital of Guangzhou Medical University, State Key Laboratory of Respiratory Disease, National Center for Respiratory Medicine, National Clinical Research Center for Respiratory Disease, Guangzhou Institute of Respiratory Health, Guangzhou, 510120, People's Republic of China; 2KingMed School of Laboratory Medicine, Guangzhou Medical University, Guangzhou, 511495, People's Republic of China; 3MRC Biostatistics Unit, University of Cambridge, Cambridge, CB2 0SR, UK; 4Guangzhou Laboratory, Guangzhou, 510005, People's Republic of China; 5Guangzhou Eighth People's Hospital, Guangzhou Medical University, Guangzhou, 510440, People's Republic of China*These authors contributed equally to this workCorrespondence: Baoqing Sun; Huimin Huang, Department of Clinical Laboratory of the First Affiliated Hospital of Guangzhou Medical University, State Key Laboratory of Respiratory Disease, National Center for Respiratory Medicine, National Clinical Research Center for Respiratory Disease, Guangzhou Institute of Respiratory Health, Guangzhou, 510120, People's Republic of China, Tel +86 13824124015 ; +86 13631496651, Email sunbaoqing@vip.163.com; huanghuimin311@126.comBackground: While serum periostin and Krebs von den Lungen-6 (KL-6) have been acknowledged as independent markers in idiopathic pulmonary fibrosis (IPF) diagnosis, the clinical combinatory potential of these biomarkers combined with high-resolution computed tomography (HRCT) has yet to be fully explored.Methods: This retrospective study involved 78 participants, comprising 51 UIP-IPF patients and 27 healthy controls. All subjects underwent clinical and laboratory examinations, particularly the detection of periostin and KL-6 using ELISA with innovative HRCT fibrosis score evaluations at admission and discharge during hospitalization in UIP-IPF patients.Results: In our cohort of patients with IPF, predominantly male, over an average follow-up period of 195.27 days. Serum levels of periostin and KL-6 were significantly elevated in IPF patients compared to healthy controls (*p < 0.05). Post-treatment, KL-6 levels decreased significantly, while periostin levels increased. Notably, periostin exhibited superior prognostic accuracy over KL-6, with a higher AUC of 0.875 than 0.639 in ROC analysis. An increase in periostin levels correlated with disease progression, as evidenced by worsened HRCT fibrotic scores and decreased survival probability. These findings underscore periostin's potential as a reliable biomarker for assessing IPF severity and therapeutic response.Conclusion: Our findings underscore the preeminence of serum periostin over KL-6 in UIP-IPF diagnosis, particularly when conjoined with HRCT fibrosis score.Keywords: periostin, Krebs von den Lungen-6, idiopathic pulmonary fibrosis, HRCT fibrosis score, diagnostic hematology